2022
DOI: 10.3390/cancers14153763
|View full text |Cite
|
Sign up to set email alerts
|

A Proof-of-Concept Inhibitor of Endothelial Lipase Suppresses Triple-Negative Breast Cancer Cells by Hijacking the Mitochondrial Function

Abstract: Triple-negative breast cancer (TNBC) cells reprogram their metabolism to provide metabolic flexibility for tumor cell growth and survival in the tumor microenvironment. While our previous findings indicated that endothelial lipase (EL/LIPG) is a hallmark of TNBC, the precise mechanism through which LIPG instigates TNBC metabolism remains undefined. Here, we report that the expression of LIPG is associated with long non-coding RNA DANCR and positively correlates with gene signatures of mitochondrial metabolism-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Additionally, DANCR has been shown to interact with proteins and mRNAs. For example, DANCR regulates endothelial lipase (EL/LIPG), a pivotal modulator of tumour cell metabolism, by binding to LIPG and modulating the stable expression of the LIPG protein in TNBC cells [27]. Moreover, studies have indicated that DANCR enhances the stability of the PSMD10 mRNA by interacting with the PSMD10 3'-UTR to counteract the inhibitory effects imposed by miRNAs such as miR-214 and miR-1254 [28].…”
Section: Downstream Regulatory Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, DANCR has been shown to interact with proteins and mRNAs. For example, DANCR regulates endothelial lipase (EL/LIPG), a pivotal modulator of tumour cell metabolism, by binding to LIPG and modulating the stable expression of the LIPG protein in TNBC cells [27]. Moreover, studies have indicated that DANCR enhances the stability of the PSMD10 mRNA by interacting with the PSMD10 3'-UTR to counteract the inhibitory effects imposed by miRNAs such as miR-214 and miR-1254 [28].…”
Section: Downstream Regulatory Mechanismsmentioning
confidence: 99%
“…Moreover, DANCR interacts with RXRA, promoting its phosphorylation and activating the PI3K/AKT signalling pathway, promoting TNBC progression [47]. Yang et al [27] [5]. In addition, miR-29b-1/a [54], lidocaine and bupivacaine [30] were shown to downregulate DANCR expression, inhibiting cancer cell progression.…”
Section: Breast Cancermentioning
confidence: 99%